Legal subjectivity in labour law in the context of relation between civil code and labour code - Šmíd, Martin (Univerzita Pardubice, 2013)
The paper deals with the actual problem of the concept of legal subjectivity in labour law in the context of relation between two main laws in this matter – Civil Code and Labour Code – which is based on the principle of subsidiarity of civil law. It analyses the problematic from a historical perspective since the distinction of labour law legal personality and capacity from classic private law legal personality and capacity in 1965 by issuing the first Labour Code (65/1965 Coll.) until the adoption of the new Civil Code in 2012 (89/2012 Coll.) through all the important historical changes (liberalization of labour market in 1990s, preparation for EU membership, adoption of New Labour Code in 2006 etc.). The conclusion is devoted to the consequences of the new Civil Code (89/2012 Coll.), which was issued in 2012 and shall be effective on 1st January 2014, for the adaptation of labour law in the area of legal subjectivity.
Keywords: labour law; civil law; legal personality; legal capacity; new civil code; employer; employee